Silver electrode material with ordered through-pore structure and preparation method thereof

Through the electrochemical oxidation and reduction process, combined with the use of silver nets, silver electrode materials with a through-pore structure were prepared, which solved the problems of cumbersome methods and single structural size in the prior art, and achieved efficient electrolyte diffusion and excellent electrochemical properties.

CN115287729BActive Publication Date: 2025-03-07TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110408718.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-16
Publication Date
2025-03-07
Estimated Expiration
2041-04-16

AI Technical Summary

Technical Problem

In the prior art, the method of preparing an ordered through-pore structure is complicated, the structure size is single, and the application range is narrow, making it difficult to flexibly adjust the electrode structure size.

Method used

Through the electrochemical oxidation and electrochemical reduction processes, the speed of silver atom redox and microcrystal deposition is regulated, and combined with the use of silver nets, a column-like structure array of silver electrode materials is prepared to form straight or approximately straight through-pore structures.

Benefits of technology

The efficient diffusion of electrolyte in silver electrode materials is achieved, the polarization effect and overpotential of electrodes are reduced, and the electrochemical performance and preparation efficiency of silver electrode materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115287729B_ABST
    Figure CN115287729B_ABST
Patent Text Reader

Abstract

The present invention discloses a silver electrode material with an ordered straight-through pore structure, wherein a columnar structure array composed of silver nanoparticles is distributed on the surface of the silver electrode material, and the gaps between the columnar structures are straight or approximately straight straight-through pores in the direction perpendicular to the surface of the silver electrode material; wherein the lateral size of the columnar structure is 0.1 to 20 μm, the height of the columnar structure is 0.2 to 1.4 mm, and the gaps between the columnar structures are 0.01 to 10.0 μm. The straight-through pore structure is conducive to improving the diffusion rate of the electrolyte, improving the exchange rate of reactants and products on the electrode surface during the electrochemical reaction, and improving the reaction rate; at the same time, the conductivity of the columnar structure composed of nanosilver is higher than that of the ordinary silver powder electrode, which is conducive to the transmission of electrons in the electrode body. Therefore, the polarization effect and overpotential of the silver electrode material in the present invention are lower, and the electrochemical performance is better. In addition, the present invention also provides a preparation method of the silver electrode material, which is simple in process, easy to operate, convenient in parameter control, more flexible in process, and higher in preparation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and more specifically, to a silver electrode material with an ordered through-pore structure and a preparation method thereof. Background Art

[0002] Silver electrodes are widely used in voltammetric analysis, piezoelectric analysis, spectral analysis, and wave spectrum analysis due to their unique physicochemical and electrochemical properties. Traditional silver electrodes are typical porous electrodes with disordered arrangement of microscopic particles. The formed pore tortuosity is large, which is not conducive to the diffusion of electrolytes. During the electrochemical reaction, the electrolyte diffusion is not smooth, polarization is severe, and the overpotential is large. The appearance of ordered straight-through pore structures in electrode materials is generally considered to be conducive to the diffusion of electrolytes, and plays an important role in obtaining high current density and improving cycle performance.

[0003] Many researchers at home and abroad use positive alumina template method, photolithography, self-organization method, etc. to prepare ordered silver electrode materials. The positive alumina template method requires the use of oxalic acid or phosphoric acid solution to adjust the positive oxidation voltage and etching time to control the diameter of the alumina nanopores (M. Muhammad, B. Yan, G. Yao, K. Chao, C. Zhu, Q. Huang, Surface-Enhanced Raman Spectroscopy for Trace Detection of Tetracycline and Dicyandiamide in Milk Using Transparent Substrate of Ag Nanoparticle Arrays, ACS Applied Nano Materials 3 (2020) 7066-7075.). The size of the ordered structured silver deposited using this template is specific. If the size of the ordered structured silver needs to be changed, the template needs to be prepared again. The template method prepares ordered structured silver, and the ordered array is uniform, but the method is cumbersome, the structure size is single, and the application range is narrow. The photoresist method uses a photolithography process to cover a layer of photoresist with a micropore array on the surface of a flat high-purity zinc sheet (Zuo Jie. Preparation of ordered arrays of silver nano-dendritic clusters and their SERS activity [D]. Hefei: Hefei Institutes of Physical Science, University of Chinese Academy of Sciences, 2016). The processed zinc sheet is then immersed in a mixed solution of AgNO3 and citric acid in a certain ratio. Due to the limitation of the micropores on the surface of the zinc sheet, Ag +The galvanic replacement reaction between Zn and Zn is limited within the scope of the exposed zinc sheet, and a bundle of independent silver nano dendrite clusters grows in each micropore. The photoresist method is similar to the template method. The prepared silver nano dendrite clusters are related to the micropore size of the photoresist. If silver nano crystal clusters of different sizes need to be prepared, photoresists of different micropore sizes are required. The self-organization method is to obtain a stable monodisperse silver nano particle sol through a liquid-liquid two-phase transfer method. The sol can self-organize to form an ordered two-dimensional nano array (Shengtai He, JY, Peng Jiang, Dongxia Shi, Haoxu Zhang, SP, Sishen Xie, and Hongjun Gao, Formation of silver nanoparticles and self-assembled two-dimensional ordered superlattice, Langmuir 17 (2001) 1571-1575). The self-organization method has higher requirements on the particle size distribution range of nanoparticles and the stability of the sol phase, especially, the standard deviation of the particle diameter is less than 10%.

[0004] The above preparation methods are all complicated, and the prepared silver electrode has a single structure size and a narrow application range. Therefore, it is necessary to provide a preparation method with a simple process and the ability to flexibly adjust the structure size of the silver electrode. Summary of the invention

[0005] An object of the present invention is to provide a silver electrode material with an ordered straight-through pore structure, wherein a columnar structure array composed of silver nanoparticles is distributed on the surface of the silver electrode material, and in a direction perpendicular to the surface of the silver electrode material, the gaps between the columnar structures are straight or approximately straight straight-through pore structures. The straight-through pore structure is conducive to the diffusion of electrolyte in the silver electrode material, accelerates the contact rate between the silver electrode surface and the electrolyte, reduces the polarization effect and overpotential of the electrode, and improves the electrochemical performance of the silver electrode material.

[0006] Another object of the present invention is to provide a method for preparing a silver electrode material with an ordered through-pore structure.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A silver electrode material with an ordered straight-through pore structure, wherein a columnar array composed of silver nanoparticles is distributed on the surface of the silver electrode material, and in a direction perpendicular to the surface of the silver electrode material, the gaps between the columnar structures are straight or approximately straight straight-through pore structures; wherein the lateral size of the columnar structure is 0.1 to 20 μm, the height of the columnar structure is 0.2 to 1.4 mm, and the distance between the columnar structures is 0.01 to 10.0 μm.

[0009] Preferably, the porosity of the surface of the silver electrode material is 50-85%.

[0010] It should be noted that the columnar structure in the present invention refers to a structure formed by the accumulation of silver nanoparticles that is not a regular columnar structure, such as a cylindrical shape, a flat column with a certain thickness, a rectangular column, etc. The cross-section of the columnar structure can be various regular or irregular shapes, and the size and shape of the cross-section can also change along the growth direction of the structure, but in general, its growth direction is perpendicular to the surface of the silver electrode material. The lateral size of the columnar structure in the present invention refers to the size of the straight-line distance between any two points on any cross-section of the structure, such as the diameter of a circular cross-section, the major axis size of an elliptical cross-section, the diagonal size of a rectangular, square or diamond cross-section, etc.

[0011] The surface of the silver electrode material in the present invention is distributed with a columnar structure array composed of silver nanoparticles, and in the direction perpendicular to the surface of the silver electrode material, the gaps between the columnar structures are straight or approximately straight through pore structures; that is, the substrate on which the columnar structure grows can directly contact the outside through the straight through pore structure, and when the electrode material is placed in an electrolyte, the electrolyte can diffuse through the straight through pore structure, completely infiltrate all surfaces of the electrode material, and reach the substrate.

[0012] It should be noted that the distribution of the columnar structure array in the present invention includes but is not limited to the following situations: the columnar structures are relatively loosely distributed, the distance between a single columnar structure and the surrounding adjacent nanocolumns is relatively large, and the straight-through pore structure formed is relatively dispersed and uniformly distributed on the surface of the silver nanoelectrode; the columnar structures in the array may be arranged more closely in a certain direction, showing the characteristics of being distributed in rows, and at this time the straight-through pore structure mainly exists between two adjacent rows of columnar structures.

[0013] When the silver electrode material in the present invention participates in an electrochemical reaction, on the one hand, the straight-through pore structure is conducive to increasing the diffusion rate of the electrolyte, making it easier for the reactants to diffuse to the inner surface of the electrode pores to participate in the reaction, and at the same time, the reaction products are also easier to leave the inner surface of the electrode pores, freeing up reaction sites and increasing the reaction rate.

[0014] On the other hand, the conductivity of the columnar structure of the silver electrode material is higher than that of the ordinary powder electrode, which is conducive to the transmission of electrons in the electrode body.

[0015] Therefore, the silver electrode material with ordered through-pore structure in the present invention has lower polarization effect and overpotential in electrochemical reaction, and better electrochemical performance than the traditional powder electrode.

[0016] Preferably, a silver mesh is distributed on the substrate on which the columnar structure in the silver electrode material grows; preferably, each grid in the silver mesh has a length of 2-4 mm, a width of 1-2 mm, and a diameter of the silver mesh wire of 0.3-0.6 mm.

[0017] The silver mesh can support the silver electrode material, which is conducive to the preparation of larger silver electrodes. At the same time, when the silver mesh is distributed in the substrate, more orderly columnar structures can be grown on both sides of the substrate at the same time, so that the thickness of the silver electrode material is doubled, thereby improving the preparation efficiency of the material.

[0018] Preferably, the silver electrode has a sheet-like structure, both sides of the sheet-like structure have columnar structure arrays, and the thickness of the sheet-like structure is 0.5-3.0 mm.

[0019] The process of forming an ordered through-pore structure is related to the electrochemical reaction rate, the product deposition rate and the migration rate. Only when the three rates match can an electrode material with an ordered structure be obtained. Under a certain electrochemical reaction rate, the appropriate thickness of the electrode sheet can ensure that the product has enough space to migrate to the appropriate position for deposition, thereby forming an ordered structure. Since the columnar structure cannot grow indefinitely, when the silver electrode sheet is too thick, the ordered structure cannot be formed in the entire electrode sheet, and the generated electrode surface is not significantly different from that of an ordinary powder electrode, and the advantages of the through-pore structure cannot be reflected.

[0020] A method for preparing the silver electrode material with the ordered through-pore structure as described above comprises the following steps:

[0021] Placing silver powder in a mold and pressing it into a silver electrode material to be oxidized;

[0022] The silver electrode material to be oxidized is oxidized into a silver oxide electrode material through an electrochemical oxidation process;

[0023] The silver oxide electrode material is reduced to a silver electrode material through an electrochemical reduction process;

[0024] Among them, the current density during the electrochemical oxidation process is 3-50mA / cm 2 ;

[0025] The discharge rate during the electrochemical reduction process is 0.10-10C.

[0026] The present invention provides a method for preparing a silver electrode through electrochemical oxidation and electrochemical reduction processes, wherein the speed of oxidation and reduction of silver atoms in the electrochemical oxidation-reduction cycle, the speed of microcrystal deposition and the migration rate of ions under the action of an electric field are regulated so that the three rates are matched with each other, thereby preparing a silver electrode material with an ordered through-pore structure.

[0027] Preferably, the particle size of the silver powder is 50-300 nm.

[0028] The particle size of silver powder directly affects the activity of silver particles. Using silver powder that is too large or too small cannot achieve a speed that matches oxidation and deposition, and cannot obtain an ordered structure.

[0029] Preferably, the thickness of the silver electrode material to be oxidized is 0.5-3.0 mm, and the porosity is 50-85%.

[0030] A larger porosity is conducive to the diffusion of the electrolyte, but the structure is too loose and easily breaks into slag. A smaller porosity makes it difficult for the electrolyte to penetrate, and the electrochemical reaction cannot proceed normally, so it is impossible to obtain an ordered silver electrode or the prepared silver electrode microstructure is stacked in a columnar shape.

[0031] Preferably, a silver mesh is used in the process of pressing the silver electrode material to be oxidized, and the specific operation is as follows:

[0032] First add a portion of the silver powder into the mold, then lay the silver mesh on the silver powder, and then add the remaining silver powder;

[0033] In the preparation method provided by the present invention, the silver mesh has a supporting and protective effect on the silver electrode material to be oxidized, improves the mechanical strength of the material, prevents the cracking and damage of the electrode material caused by volume expansion during the preparation process, and helps to prepare a large-sized electrode material; at the same time, the silver mesh provides a channel for the uniform flow of current in the electrode material during the electrochemical oxidation and reduction process, so that the generated columnar structure material can be arranged in an orderly manner, which is conducive to the formation of straight-through pores; in addition, the addition of the silver mesh realizes the electrochemical oxidation-reduction reaction on both sides of the electrode material, and the growth of columnar structures arranged in an orderly manner can be carried out on both sides of the silver mesh at the same time, and the thickness of the electrode material can be doubled, which improves the preparation efficiency of the material. In the present invention, the silver mesh is used as a supporting mesh, which effectively avoids the introduction of impurities and can be well integrated with the base of the silver electrode material.

[0034] In the actual application process, the size of the silver mesh is very important for the orderly growth of the columnar structure. If the silver mesh is too large, the current distribution uniformity in the electrode material is not high, the growth of the columnar structure is limited, the degree of order is reduced, and only messy gravel-like crystal particles can be obtained, and the gaps between them cannot form straight-through pores that are approximately straight, which has a negative impact on the electrochemical properties of the electrode material. On the contrary, if the mesh of the silver mesh is too small, the silver powder is separated to a large extent and cannot form a whole with sufficient strength. It is easy to disintegrate during the preparation process, and the preparation of the target material cannot be achieved. Therefore, the size of the silver mesh provided in the present invention is preferably that the length of each grid in the silver mesh is 2-4mm, the width is 1-2mm, and the diameter of the silver mesh wire is 0.3-0.6mm.

[0035] Preferably, the electrochemical oxidation process is constant current oxidation or step current oxidation; the duration of the electrochemical oxidation process is 3-80 hours.

[0036] Preferably, the counter electrode material used in the electrochemical oxidation process is stainless steel or platinum.

[0037] Preferably, the electrolytes in both the electrochemical oxidation process and the electrochemical reduction process are alkaline solutions.

[0038] Preferably, the concentration of the alkaline solution is 0.03-0.50 g / cm 3 ; The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0039] One possible implementation method is that during the electrochemical oxidation process, a suitable counter electrode is selected according to the size of the silver electrode material to be oxidized, the two electrodes are placed together in an alkaline solution, the silver electrode material to be oxidized is connected to the positive electrode of the power supply, and the counter electrode is connected to the negative electrode of the power supply to form a battery series system. 2 The silver oxide electrode material is subjected to constant current or step current electrochemical oxidation at a current density of 3 to 80 hours. After the electrochemical oxidation is completed, the material is taken out, soaked and washed with deionized water until neutral, taken out, and placed in a vacuum drying oven for drying. A hair dryer can also be used to accelerate the drying and then naturally dried to obtain a silver oxide electrode material.

[0040] One possible implementation method is that during the electrochemical reduction process, the silver oxide electrode material and the aluminum alloy electrode are placed in an alkaline solution, the aluminum alloy electrode is connected to the positive electrode of the power supply, and the silver oxide electrode material is connected to the negative electrode of the power supply to form a battery series system for discharge (i.e., electrochemical reduction). After the discharge is completed, the material is taken out, soaked and washed with deionized water until neutral, taken out, placed in a vacuum drying oven to dry, or dried naturally with a hair dryer to accelerate the drying, so as to obtain a silver electrode material with an ordered structure.

[0041] The preparation process of the silver electrode material with an ordered straight-through pore structure provided by the present invention is simple and easy to operate, does not require special processes such as templates, and can prepare silver electrode materials of different sizes by adjusting process parameters. The process preparation process is more flexible and the preparation efficiency is higher.

[0042] The beneficial effects of the present invention are as follows:

[0043] The present invention provides a silver electrode material with an ordered straight-through pore structure, wherein a columnar array composed of silver nanoparticles is distributed on the surface of the silver electrode material, and in a direction perpendicular to the surface of the silver electrode material, the gaps between the columnar structures are straight or approximately straight straight-through pore structures. The straight-through pore structure is conducive to improving the diffusion rate of the electrolyte, improving the exchange rate of reactants and products on the electrode surface during the electrochemical reaction, and improving the reaction rate; at the same time, the conductivity of the columnar structure is higher than that of the powder electrode, which is conducive to the transmission of electrons in the electrode body. Therefore, the polarization effect and overpotential of the silver electrode material in the present invention are lower, and the electrochemical performance is more excellent.

[0044] In addition, the present invention also provides a method for preparing the silver electrode material, which has a simple process, is easy to operate, has convenient parameter control, has a more flexible process, and has a higher preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0046] Figure 1 A scanning electron microscope photograph of the silver electrode material prepared in Example 1 of the present invention is shown.

[0047] Figure 2 A scanning electron microscope photograph of the silver electrode material prepared in Example 2 of the present invention is shown.

[0048] Figure 3 A scanning electron microscope photograph of the silver electrode material prepared in Example 3 of the present invention is shown.

[0049] Figure 4 A scanning electron microscope photograph of the silver electrode material prepared in Example 4 of the present invention is shown.

[0050] Figure 5 A scanning electron microscope photograph of the silver electrode material prepared in Example 5 of the present invention is shown.

[0051] Figure 6 A scanning electron microscope photograph of the flaky silver electrode material in Comparative Example 1 is shown.

[0052] Figure 7 A scanning electron microscope photograph of the powdered silver electrode material in Comparative Example 2 is shown.

[0053] Figure 8 The CV curve of water electrolysis in Test Example 1 is shown.

[0054] Fig. 9 The CV curve of water electrolysis in Test Example 2 is shown. DETAILED DESCRIPTION

[0055] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0056] Example

[0057] Example 1

[0058] Weigh a certain amount of 50-300nm silver powder and place it in the mold. Add the silver powder twice, use a silver mesh with a specification of 2*4*0.6mm as the current collector in the middle, and press it into a silver sheet to be oxidized by a hydraulic press. The corresponding silver sheet to be oxidized can also be prepared by a roller pressing process. The porosity of the silver sheet to be oxidized is 75% and the thickness is 1.4mm. According to the size of the silver sheet to be oxidized, select a platinum sheet of appropriate size. The silver sheet to be oxidized and the platinum sheet are placed together with 0.04g / cm 3 In the sodium hydroxide solution, the silver sheet to be oxidized is connected to the positive electrode of the power supply, and the platinum sheet is connected to the negative electrode of the power supply to form a battery series system. 2 The pressed silver sheet to be oxidized was subjected to constant current electrochemical oxidation at a current density of , and the oxidation time was 30 hours. After the electrochemical oxidation was completed, it was taken out, soaked and washed with deionized water until neutral, taken out, accelerated drying with a hair dryer, and then naturally dried to obtain a silver oxide sheet. The prepared silver oxide sheet and aluminum alloy sheet were placed in a 0.04g / cm 3 In a sodium hydroxide solution, the aluminum alloy sheet is connected to the positive electrode of the power supply, and the silver oxide sheet is connected to the negative electrode of the power supply to form a battery series system. The battery is discharged at a rate of 0.5C (i.e., electrochemical reduction). After the discharge is completed, the battery is taken out, soaked and washed with deionized water until neutral, and dried naturally after accelerated drying with a hair dryer to obtain a silver electrode material with an ordered straight-through pore structure. Figure 1 As shown, under a scanning electron microscope (HITACHI S-4800) with a magnification of 1k times, it can be clearly observed that the ordered structure is in the shape of flat columns, and the gaps between the columns are straight-through pores that are approximately straight lines.

[0059] Example 2

[0060] Weigh a certain amount of 50-300nm silver powder and place it in the mold. Add the silver powder twice, use a silver mesh with a specification of 2*4*0.6mm as the current collector in the middle, and press it into a silver sheet to be oxidized by a hydraulic press. The corresponding silver sheet to be oxidized can also be prepared by a roller pressing process. The porosity of the silver sheet to be oxidized is 70% and the thickness is 2.1mm. According to the size of the silver sheet to be oxidized, choose a stainless steel sheet of appropriate size. The silver sheet to be oxidized and the stainless steel sheet are placed together with 0.08g / cm 3In the potassium hydroxide solution, the silver sheet to be oxidized is connected to the positive electrode of the power supply, and the stainless steel sheet is connected to the negative electrode of the power supply to form a battery series system. 2 The pressed silver sheet to be oxidized was subjected to constant current electrochemical oxidation at a current density of , and the oxidation time was 40.5 h. After the electrochemical oxidation was completed, it was taken out, soaked and washed with deionized water until neutral, dried with a hair dryer to accelerate drying, and then dried naturally to obtain a silver oxide sheet. The prepared silver oxide sheet and aluminum alloy sheet were placed in a 0.08 g / cm 3 In a potassium hydroxide solution, the aluminum alloy sheet is connected to the positive electrode of the power supply, and the silver oxide sheet is connected to the negative electrode of the power supply to form a battery series system. The battery is discharged at a rate of 5C (i.e., electrochemical reduction). After the discharge is completed, the battery is taken out, soaked and washed with deionized water until it is neutral, taken out, and dried naturally after accelerated drying with a hair dryer to obtain a silver electrode material with an ordered straight-through pore structure. Figure 2 As shown, the columnar structure grows perpendicular to the substrate. Under a scanning electron microscope (HITACHI S-4800) with a magnification of 1k times, it can be clearly observed that the top of the columnar structure is spike-shaped or cylindrical, and the gaps in the columnar structure are straight-through pores that are approximately straight lines.

[0061] Example 3

[0062] Weigh a certain amount of 50-300nm silver powder and place it in the mold. Add the silver powder twice, use a silver mesh with a specification of 2*4*0.6mm as the current collector in the middle, and press it into a silver sheet to be oxidized by a hydraulic press. The corresponding silver sheet to be oxidized can also be prepared by a roller pressing process. The porosity of the silver sheet to be oxidized is 60% and the thickness is 2.1mm. According to the size of the silver sheet to be oxidized, select a platinum sheet of appropriate size. The silver sheet to be oxidized and the platinum sheet are placed together with 0.32g / cm 3 In the sodium hydroxide solution, the silver sheet to be oxidized is connected to the positive electrode of the power supply, and the platinum sheet is connected to the negative electrode of the power supply to form a battery series system. 2 The pressed silver sheet to be oxidized was subjected to constant current electrochemical oxidation at a current density of , and the oxidation time was 36 hours. After the electrochemical oxidation was completed, it was taken out, soaked and washed with deionized water until neutral, taken out, placed in a vacuum drying oven to dry, and the silver oxide sheet was obtained after drying. The prepared silver oxide sheet and aluminum alloy sheet were placed in a 0.32g / cm 3 In a sodium hydroxide solution, the aluminum alloy sheet is connected to the positive electrode of the power supply, and the silver oxide sheet is connected to the negative electrode of the power supply to form a battery series system. The battery is discharged at a rate of 3C (i.e., electrochemical reduction). After the discharge is completed, the battery is taken out and washed with deionized water until it is neutral. The battery is placed in a vacuum drying oven to dry. A hair dryer can also be used to accelerate the drying and then naturally dried to obtain a silver electrode material with an ordered straight-through pore structure. Figure 3As shown, under a scanning electron microscope (HITACHI S-4800) with a magnification of 2k times, the columnar structure can be clearly observed. The columnar structures in the array structure are closely arranged in rows, and the gaps between the rows are obvious, which are straight-through pores similar to straight lines.

[0063] Example 4

[0064] Weigh a certain amount of 50-300nm silver powder and place it in the mold. Add the silver powder twice, use a silver mesh with a specification of 1*2*0.3mm as the current collector in the middle, and press it into a silver sheet to be oxidized by a hydraulic press. The corresponding silver sheet to be oxidized can also be prepared by a roller pressing process. The porosity of the silver sheet to be oxidized is 80% and the thickness is 1.4mm. According to the size of the silver sheet to be oxidized, select a platinum sheet of appropriate size. The silver sheet to be oxidized and the platinum sheet are placed together with 0.16g / cm 3 In the sodium hydroxide solution, the silver sheet to be oxidized is connected to the positive electrode of the power supply, and the platinum sheet is connected to the negative electrode of the power supply to form a battery series system. 2 The pressed silver sheet to be oxidized was subjected to constant current electrochemical oxidation at a current density of , and the oxidation time was 24h. After the electrochemical oxidation was completed, it was taken out, soaked and washed with deionized water until neutral, taken out, placed in a vacuum drying oven to dry, and the silver oxide sheet was obtained after drying. The prepared silver oxide sheet and aluminum alloy sheet were placed in a 0.16g / cm 3 In a sodium hydroxide solution, the aluminum alloy sheet is connected to the positive electrode of the power supply, and the silver oxide sheet is connected to the negative electrode of the power supply to form a battery series system. The battery is discharged at a rate of 7C (i.e., electrochemical reduction). After the discharge is completed, the battery is taken out and washed with deionized water until it is neutral. The battery is then placed in a vacuum drying oven and dried to obtain a silver electrode material with an ordered straight-through pore structure. The columnar structure grows perpendicular to the direction of the silver mesh substrate, such as Figure 4 As shown, under a scanning electron microscope (HITACHI S-4800) with a magnification of 1k times, it can be clearly observed that the columnar structures in the array are arranged in rows, with large gaps between rows, and straight-through pores that are quasi-straight lines.

[0065] Example 5

[0066] Weigh a certain amount of 50-300nm silver powder and place it in the mold. Add the silver powder twice, use a silver mesh with a specification of 2*4*0.6mm as the current collector in the middle, and press it into a silver sheet to be oxidized by a hydraulic press. The corresponding silver sheet to be oxidized can also be prepared by a roller pressing process. The porosity of the silver sheet to be oxidized is 65% and the thickness is 1.4mm. According to the size of the silver sheet to be oxidized, select a platinum sheet of appropriate size. The silver sheet to be oxidized and the platinum sheet are placed together with 0.16g / cm 3 In the sodium hydroxide solution, the silver sheet to be oxidized is connected to the positive electrode of the power supply, and the platinum sheet is connected to the negative electrode of the power supply to form a battery series system.2 The pressed silver sheet to be oxidized was subjected to constant current electrochemical oxidation at a current density of , and the oxidation time was 42 hours. After the electrochemical oxidation was completed, it was taken out, soaked and washed with deionized water until neutral, taken out, placed in a vacuum drying oven to dry, and the silver oxide sheet was obtained after drying. The prepared silver oxide sheet and aluminum alloy sheet were placed in a 0.16g / cm 3 In a sodium hydroxide solution, the aluminum alloy sheet is connected to the positive electrode of the power supply, and the silver oxide sheet is connected to the negative electrode of the power supply to form a battery series system. The battery is discharged at a rate of 1C (i.e., electrochemical reduction). After the discharge is completed, the battery is taken out, washed with deionized water until neutral, and then placed in a vacuum drying oven to dry, thereby obtaining a silver electrode material with an ordered through-hole structure. Figure 5 As shown, under a scanning electron microscope (HITACHI S-4800) with a magnification of 1k times, it can be clearly observed that the particles are stacked and arranged to form a columnar structure with a certain gap in the middle, forming straight or approximately straight through pores.

[0067] Comparative Example 1

[0068] The sheet silver electrode is a silver metal sheet purchased directly, which is cut into sheets with the same area as the electrode to be tested. The structure is as follows: Figure 6 As shown, the horizontal lines in the photo are traces of sandpaper polishing.

[0069] Comparative Example 2

[0070] The silver electrode sheet to be oxidized prepared in Example 5 can be used as Comparative Example 2. The silver electrode sheet to be oxidized is a powder electrode, and its structure is as follows: Figure 7 shown.

[0071] Test Example 1

[0072] The silver electrode with ordered through-pore structure prepared in Example 5, the sheet silver electrode prepared in Comparative Example 1, and the powdered silver electrode prepared in Comparative Example 2 were used as cathodes, and platinum sheets were used as anodes to electrolyze water. H2SO4 solution was selected as the electrolyte. The CV curves of the electrolyzed water are shown in FIG. Figure 8 shown.

[0073] Test Example 2

[0074] The silver electrode with ordered through-pore structure prepared in Example 5, the sheet silver electrode prepared in Comparative Example 1, and the powdered silver electrode prepared in Comparative Example 2 were used as cathodes, and platinum sheets were used as anodes to electrolyze water. NaOH solution was selected as the electrolyte. The CV curves of the electrolyzed water are shown in FIG. Fig. 9 shown.

[0075] It can be seen from the test results of Test Examples 1 and 2 that the silver electrode with a through-pore structure of the present invention has a lower electrolytic cell voltage under the same current density compared with other electrodes, and the reduction is more obvious as the electrolysis current increases. Therefore, it is beneficial to energy saving in the water electrolysis process, and a larger electrolysis current can be achieved under a given electrolytic cell voltage, thereby improving production efficiency.

[0076] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A silver electrode material with an ordered through-pore structure, characterized in that: The surface of the silver electrode material is distributed with a columnar structure array composed of silver nanoparticles, and in the direction perpendicular to the surface of the silver electrode material, the gaps between the columnar structures are straight or approximately straight through pore structures; wherein the lateral size of the columnar structure is 0.1 to 20 μm, the height of the columnar structure is 0.2 to 1.4 mm, and the distance between adjacent columnar structures is 0.01 to 10.0 μm; A silver mesh is distributed on the substrate on which the columnar structure of the silver electrode material grows; each grid in the silver mesh has a length of 2-4 mm, a width of 1-2 mm, and a diameter of the silver mesh wire of 0.3-0.6 mm; The silver electrode material is prepared according to the following steps: Placing silver powder in a mold to press the silver electrode material to be oxidized; The silver electrode material to be oxidized is oxidized into a silver oxide electrode material through an electrochemical oxidation process; The silver oxide electrode material is reduced to a silver electrode material through an electrochemical reduction process; Among them, the current density during the electrochemical oxidation process is 3-50mA / cm 2 ; The discharge rate during electrochemical reduction is 0.10-10C; The particle size of the silver powder is 50-300nm; the porosity of the surface of the silver electrode material is 50-85%; the silver electrode has a sheet structure, both sides of the sheet structure have columnar structure arrays, and the thickness of the sheet structure is 0.5-3.0mm.

2. A method for preparing the silver electrode material as claimed in claim 1, characterized in that: The following steps are involved: Placing silver powder in a mold to press the silver electrode material to be oxidized; The silver electrode material to be oxidized is oxidized into a silver oxide electrode material through an electrochemical oxidation process; The silver oxide electrode material is reduced to a silver electrode material through an electrochemical reduction process; Among them, the current density during the electrochemical oxidation process is 3-50mA / cm 2 ; The discharge rate during electrochemical reduction is 0.10-10C; The particle size of the silver powder is 50-300nm; The thickness of the silver electrode material to be oxidized is 0.5-3.0 mm, and the porosity is 50-85%; Silver mesh is used during the pressing of the silver electrode material to be oxidized.

3. The preparation method according to claim 2, characterized in that: The specific operation of using silver mesh in the process of pressing the silver electrode material to be oxidized is: First add a portion of the silver powder into the mold, then place the silver mesh on the silver powder, and then add the remaining silver powder.

4. The preparation method according to claim 2, characterized in that: The length of each grid in the silver mesh is 2-4 mm, the width is 1-2 mm, and the diameter of the silver mesh wire is 0.3-0.6 mm.

5. The preparation method according to claim 2, characterized in that: The electrochemical oxidation process is constant current oxidation or step current oxidation; the duration of the electrochemical oxidation process is 3-80 hours.

6. The preparation method according to claim 2, characterized in that: The counter electrode material used in the electrochemical oxidation process is stainless steel or platinum.

7. The preparation method according to claim 2, characterized in that: The electrolyte in both the electrochemical oxidation process and the electrochemical reduction process is an alkaline solution.

8. The preparation method according to claim 2, characterized in that: The concentration of the alkaline solution is 0.03-0.50 g / cm 3 ; The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

Citation Information

Patent Citations

  • Method for preparing active silver electrode

    CN101235515A

  • Preparation method of spiny silver peroxide anode material

    CN102945957A